Impact of head and neck leprosy presentations on the daily lives of people with the disease (Research, Society and Development, 2021)
Leprosy is a chronic infectious and transmissible disease, of compulsory notification and investigation in the entire national territory. The objective of this study was to evaluate the impact of head and neck clinical presentations on the daily life of people affected by leprosy. This is an exploratory, descriptive study, using a qualitative approach, carried out at a reference health unit for leprosy treatment, in Maceió. A semi-structured form was applied regarding the impacts on the daily lives of the participants affected by leprosy. Six factors were identified, as they stood out regarding the impact of leprosy on the daily lives of these patients. This perception resulted in six thematic categories, namely: the Path taken to reach the diagnosis of leprosy; Experience and feelings of people affected by leprosy; Changes in social, family and professional life; Impact of the head and neck presentations of the disease on the daily lives of people affected by leprosy; social Stigma and environment; and, Overcoming the difficulties arising from the head and neck presentations of the disease. Thus, leprosy has a significant impact on the daily lives of people affected by the disease. Early diagnosis, proper treatment and continuous multiprofessional and qualified follow-up are extremely important.